Pelaksanaan Pekerjaan Cut and Fill Pada Proyek Pembangunan Kawasan PT. PLIE Karawang Jawa Barat - Ardi Ariansyah; Yusup Yulianto; Endang Setiadi Permana (FAKULTAS TEKNIK UNIVERSITAS SUBANG, 2022)
The Independent Campus Learning Program (MBKM) is carried out at the Civil Engineering Study Program, Faculty of Engineering, University of Subang, which is a program to apply various knowledge that has been acquired during learning. Implementation of MBKM activities at PT. Wan Arta nata (WAN) performs Cut and Fill work related to the PT. PLIE Kerawang, West Java. The method for implementing MBKM activities is with a qualitative descriptive approach through direct observation in the field. The results of the MBKM activities related to the implementation of the Cut and Fill work show that there were problems related to the increase in fuel oil fuel, external disturbances during the project carried out by NGOs wanting 30% so that it had an impact on the delivery of material needed by the project, natural disturbances in the form of rain, and there was mud in the excavation soil causes an effect on the stability of the embankment (soil structure) to a reduction in soil strength. The things that can be completed include holding meetings to achieve 50% of the material delivery needs, arranging work sequences and extending project time, adding heavy equipment and fleet according to the target, and drying the mud area at the project site.